Investigating EFL teachers' perceptions of technology use on student engagement: A pilot study in Turkiye - Betül Yoldaş (Journal of Language, Literature, Social and Cultural Studies, 2026)
The present pilot study aims to demonstrate EFL teachers’ perceptions of their own technology use on student engagement in language classrooms. 21 EFL teachers (17 females & 4 males) were reached with the snowball data collection technique. Teachers completed an online questionnaire, after they were taken their written consent by clicking a consent box on the form. Through qualitative research design, perceptions of EFL teachers towards their use of digital tools and reasons behind them were revealed. The results of the pilot study indicate that both experienced and less experienced teachers prefer to use themselves technology frequently in their language classrooms via computers or smart boards especially for listening and vocabulary acquisition exercises. Moreover, they prefer to use teaching videos before preparing their teaching content and during the class. Thus, teachers stated that students are more influenced affectively and classes become more joyful due to technological use in the class. None of the participant teachers were against the use of technology in language classrooms.